Supratarsal Injection of Bevacizumab in the Treatment of Vernal Kerato Conjunctivitis: Doi: 10.36351/pjo.v40i2.1767 - Kamil, Zeeshan; Ahmed, Fatima; Naz, Saliha; Muhammad Tanweer Hassan Khan (Pakistan Journal of Ophthalmology, 2024)
Purpose: To evaluate the effectiveness of supratarsal injection of Bevacizumab in the treatment of Vernal Kerato-conjunctivitis (VKC). Study Design: Quasi experimental study. Place and Duration of Study: LRBT Karachi from September 2022 to September 2023. Methods: This study included 110 eyes of 60 patients with VKC and divided into two groups by convenient sampling. In one group (n=30) 0.1ml of Bevacizumab 2.5%was injected in supratarsal space with 27-gauge needle under topical anaesthesia. Other group (n=30) received conventional treatment. The sign and symptoms were checked at one week and at one month in all patients. The qualitative variables were presented as frequency and percentage while quantitative variables were shown as mean ± standard deviation. Chi square test was applied for comparison. Results: Mean age of the patients was 12.4 +1.9 years. There were 46 (76.0%) males. Itching and photophobia was not seen in 50% of the patients treated with Bevacizumab while this percentage was 13.3% and 10% respectively in case of conventional treatment. Similarly, redness, discharge and limbal papillae were not seen in 70%, 73.3% and 83.3% respectively after Bevacizumab application. While it was 16.6%, 30% and 10% respectively after conventional treatment. Significant improvement in itching, photophobia, redness, discharge and limbal papilla was observed in the group of patients who received supratarsal Bevacizumab injection as compared to those who received conventional treatment (p<0.05). Conclusion: Bevacizumab is a safe and effective treatment in patients of VKC refractory to conventional treatment.